Combined detectors of charged particles based on zinc selenide scintillators and silicon photodiodes - Ryzhikov, V.D.; Gal’chinetskii, L.P.; Starzhinskiy, N.G.; Danshin, E.A.; Katrunov, K.A.; Chernikov, V.V. (Вопросы атомной науки и техники, 2001)
Combined detectors of charged particles are described based on zinc selenide (ZnSe(Te)) crystals, silicon photodiodes and charge-sensitive amplifiers. ZnSe(Te) scintillators are characterized by high alpha to beta ratio (~1.0), good scintillation efficiency (up to 22%), and high radiation stability (up to 100 Mrad), together with good spectral matching with silicon PIN photodiodes. The signals coming from the photodiode in the two modes (photoreceiver and semiconductor detector) differ in the amplitude values and pulse duration, which opens new possibilities for development and application of such combined detectors.